Characteristics of kangaroo-related motor vehicle crashes. Issue 9 (September 2022) - Wilson, Tamalee M; Park, Hyerin; Parys, Simon; Rao, Sudhakar
Abstract: Background: Kangaroo-related motor vehicle collisions are common but there is limited literature on this topic. Drivers confronted by kangaroos may choose to swerve or to directly collide with the kangaroo. The effect of these differing crash mechanisms, along with the effect of vehicle type or time of day, has not yet been reported. Methods: A retrospective cohort study was performed, examining patients admitted to our tertiary trauma centre for kangaroo-related motor vehicle collisions between 2000 and 2020. Data on patient demographics, crash characteristics, and hospital stay were collected and analysed. Results: A total of 366 patients were included and were predominantly male (76%) with an median age of 40. Swerve crashes were more common (59%) than direct impact and swerving was a statistically significant predictor of reduced injury severity score on multivariable analysis (other significant factors were female sex and no rollover). Motor vehicle crashes and motorbike crashes had differing crash characteristics. Motor vehicle crashes were more likely the result of swerving, and swerving was less likely to cause ejection or require extrication but more likely to cause rollover. Motorbike crashes however, were more likely the result of head on collision and riders were more likely to be ejected from the vehicle, require extrication, or be involved in a rollover. In terms of time of day, there were more crashes at dawn and there was a trend towards higher injury severity score and length of stay for night-time crashes. Conclusion: For kangaroo-related motor vehicle crashes, predictors of increased injury severity score on multivariable analysis were male sex, direct impact, and rollover. Motorbikes and motor vehicles had differing crash mechanisms and characteristics, as did night-time crashes when compared to daytime or twilight crashes. Level of evidence: IV, prognostic